Real time model for hand gesture recognition of traffic policeman - Neeraj Varshney, Paras Upadhyay, Udit Arora,Shivam Singhal, Shashank Mittal (International Journal of Advanced Science and Technology, 2020)
The detection of human movements has become a very important topic in computer vision.The intent of this survey is to provide a detailed overview of current issues and patterns, and categories. Human hand gesture movement recognition can be performed at different abstraction levels. This survey focuses on approaches aimed at acknowledging hand signals from the traffic police. The identification mechanism has been explored with many applications and algorithms. Description of traffic control signals and their various implementations were discussed in this article. Representation of the action, identification of human action, extraction of features and recognition of human action were also discussed in this paper.